Peculiarities of Physical Activity and Self‑Esteem of Young People with Diabetes Mellitus Type 1 and Healthy Persons Aged 18–25 Years (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. Careful diabetes control slows the onset and progression of life-threatening complications, the development of disability and early disability-related unemployment, and prolongs life expectancy (Danytė et al., 2000). The benefits of physical activity on regular basis comprise improved cardiovascular health, increased  lean body mass, improved  blood lipid profile, enhanced  psycho-social wellbeing and decreased obesity  (Riddell, Iscoe, 2006). Physical activity is one of the main factors influencing glucose level in diabetic patients’ blood (Wiśniewski, 2010). Analysis of self-esteem of the studied revealed a wide range of findings, from trying to outline the modest achievements, pride, and even unwillingness to discuss it to low self-esteem, feeling of guilt and self-reproach for mistakes and failures (Žemaitis, 1995). The aim of the study was to determine physical activity and self-esteem of healthy subjects and patients with diabetes mellitus type 1 aged 18–25 years.Methods. The  study  included  140  individuals  (aged  from  18  to  25  years). Among  41  patients  with  type  1 diabetes mellitus there were 33 young women and 8 young men, and among 99 healthy persons – 79 young women and  29 young men. All the subjects were asked to fill in the questionnaire orientated to physical activity and self-esteem. The short IPAQ questionnaire was used to research physical activity and Rosenberg’s Self-Esteem Scale was used to assess self esteem.Research results. Approximately 60% of subjects with  diabetes mellitus type 1 and about 50% of healthy persons rated their physical activity as moderate. Intensive 60-minute-physical activity was reported by 48.5% of healthy subjects and 34.1% of diabetic patients, moderate 60-minute-physical activity was pointed out by 38.2% of diabetic patients and 35.8% of healthy research participants. The largest walking interval was 1–1.5 hours: in the diabetic group– 28.8%, in the healthy group – 31.65%. Healthy young men and women were physically more active than diabetic patients. Self-esteem in both genders of healthy subjects and diabetic patients was determined as moderate.Discussion and conclusions. Physical activity of women and men with diabetes mellitus type 1 aged 18–25 years was valued as moderate, meanwhile physical activity in healthy persons – moderate or high. Self-esteem is moderate in both groups of patients with diabetes and healthy persons. Healthy men are more active than diabetic patients, similarly, women having diabetes mellitus type 1 are more physically passive than healthy ones. Both patients with diabetes mellitus type 1 and healthy individuals aged 18–25 reported moderate self-esteem.Keywords: diabetes mellitus type 1, physical activity, self-esteem.